2011
DOI: 10.4331/wjbc.v2.i4.67
|View full text |Cite
|
Sign up to set email alerts
|

Emanuel Strehler’s work on calcium pumps and calcium signaling

Abstract: Cells are equipped with mechanisms to control tightly the influx, efflux and resting level of free calcium (Ca 2+ ). Inappropriate Ca 2+ signaling and abnormal Ca 2+ levels are involved in many clinical disorders including heart disease, Alzheimer's disease and stroke. Ca 2+ also plays a major role in cell growth, differentiation and motility; disturbances in these processes underlie cell transformation and the progression of cancer. Accordingly, research in the Strehler laboratory is focused on a better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Both abnormal Ca 2+ levels and inappropriate Ca 2+ signaling are related to many clinical disorders such as stroke, obesity, cardiac dysfunction, aging and Alzheimer's disease [22][23][24][25]. It is worth noting that Ca 2+ signaling is a key element of apoptotic signaling pathways.…”
Section: +mentioning
confidence: 99%
“…Both abnormal Ca 2+ levels and inappropriate Ca 2+ signaling are related to many clinical disorders such as stroke, obesity, cardiac dysfunction, aging and Alzheimer's disease [22][23][24][25]. It is worth noting that Ca 2+ signaling is a key element of apoptotic signaling pathways.…”
Section: +mentioning
confidence: 99%
“…The above analysis shows that Ca 2+ can affect AD. Strehler (42) already found that the CALML3 gene is involved in the transport of Ca 2+ . Therefore, the gene CALML3 will affect the onset of AD.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in the number of apoptotic between the groups treated with 2 W/m 2 and 4 W/m 2 UVB irradiation, thus 2 W/m 2 UVB irradiation was used in subsequent experiments. To further determine the effects of UVB irradiation on apoptosis of HLECs, the cells were also treated with 2 W/m 2 UVB for various durations (5,15,30,60, 90, 120 and 180 min). After 15 min irradiation, the number of apoptotic cells ~4.2%, and the percent of apoptotic cells was increased with the increasing duration of UVB irradiation (Fig.…”
Section: Uvb Induces Apoptosis Of Hlecsmentioning
confidence: 99%
“…Cellular calcium (Ca 2+ ) homeostasis in the lens epithelial cells is essential for maintaining lens clarity. Inappropriate Ca 2+ signaling and abnormal Ca 2+ levels are associated with various clinical disorders, including stroke, cardiac dysfunction, obesity, aging and Alzheimer's diseases (15)(16)(17)(18). Ca 2+ is also involved in cell growth, differentiation and motility during the transformation and progression of cancer.…”
Section: Introductionmentioning
confidence: 99%